Lentiviral-Mediated Silencing of Farnesyl Pyrophosphate Synthase through RNA Interference in Mice. (22nd January 2015) - Yang, Jian; Zhao, Chen-Ze; Chen, Bin; Chen, Fei; Han, Jie; Hu, Shen-Jiang
Abstract : Farnesyl pyrophosphate synthase (FPPS) plays a vital role in the mevalonate pathway and has been shown to be involved in hypertrophy and cardiovascular diseases. Lentivirus-mediated RNA interference (RNAi) to knock down a gene of interest has become a promising new tool for the establishment of transgenic animals. The interfering fragment, named pLVT202, was chosen from cardiomyocytes tested in vitro and was microinjected into the perivitelline space of zygotes from C57BL/6J mice via a lentivirus vehicle; 20 were identified as carrying copies of the transgene using the polymerase chain reaction (PCR). Real-time PCR and western blotting analysis showed that FPPS was downregulated in multiple tissues in the transgenic mice. The transgenic mouse model provides a novel means of studying the gene function of FPPS.